The Influence of Work Culture And Discipline on The Performance of Employee Implementing Health Services at Kramat Jati Hospital - Desi Yanti, Desi Yanti (LPPM Universitas Respati Indonesia, 2023)
This study aims to examine the effect of work culture and discipline on the performance of health service implementers at Kramat Jati Hospital. This research uses quantitative methods, this research has been carried out at Kramat Jati Hospital using 72 samples of respondents from health service implementing employees as the main instrument in obtaining data. This analysis uses Structural Equation Modeling (SEM). The results of the study show that: Work Culture (X1) has a positive and significant effect on Performance (Y) with the original sample value of 0.838. Second; Discipline (X2) has a positive and significant effect on performance (Y) with the original sample value of 0.528. Third; Work Culture (X1) has a positive and significant effect on Discipline (X2) with an original sample value of 0.378. So it can be concluded that in this study, Keywords: Work Culture, Discipline, Performance